2012
DOI: 10.3109/0142159x.2012.719655
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the ward and waiting room: A community-based non-clinical placement programme for Australian medical students

Abstract: Placement programmes such as this can significantly contribute to medical education, especially in supporting health in local communities and understanding the needs of the marginalised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Evaluation of the Community Based Practice Program in Australia's Monash University concluded that non-clinical placements developed student's communication skills, their appreciation of non-medical community health support, and understanding of local community health (Goodall, 2012). Similarly, the Urban and Community Health Pathway program at the Medical College of Wisconsin in the U.S. found that students favored community sessions over classroom lectures and ranked the program highly valuable to their preparation as physicians (Meurer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the Community Based Practice Program in Australia's Monash University concluded that non-clinical placements developed student's communication skills, their appreciation of non-medical community health support, and understanding of local community health (Goodall, 2012). Similarly, the Urban and Community Health Pathway program at the Medical College of Wisconsin in the U.S. found that students favored community sessions over classroom lectures and ranked the program highly valuable to their preparation as physicians (Meurer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A review of community‐based education has suggested that ‘competencies’ in public health, community development and leadership should be included as a minimum requirement . This review recognised that an understanding of social accountability is at the core of community‐based education, and highlights the potential role that the PDC and similar non‐clinical models of engagement play in helping to understand the needs of the under‐represented in society …”
Section: Discussionmentioning
confidence: 99%
“…Female, 22 years 'Working with young people from lower socio-economic backgrounds gives a useful insight into this type of community, something which we may not see on placement or within our medical class…' Female, 26 years the needs of the underrepresented in society. 6 Junior doctors who undertook community work placements commented on the learned value of a holistic approach, with an increased awareness of patients' home circumstances and less focus on 'the disease, the problem, the physical' . 3 It is well documented in the literature that community-based placements in the form of student-led clinics enhance both clinical and communicative skills, with improved patient education.…”
Section: Discussionmentioning
confidence: 99%
“…And, at what stage of their training should they be exposed to children with disabilities? Research confirms undergraduates benefit from non‐clinical community placement in their pre‐clinical years . Students have reported more confidence in communication, increased empathy, and better understanding and appreciation of the challenges and contributions by allied staff.…”
mentioning
confidence: 82%
“…Research confirms undergraduates benefit from non-clinical community placement in their pre-clinical years. 4 Students have reported more confidence in communication, increased empathy, and better understanding and appreciation of the challenges and contributions by allied staff. However, in Australia, most community engagement of students has been with adults receiving care from major non-government organisations and general practices.…”
Section: What This Paper Addsmentioning
confidence: 99%